Pengaruh Substitusi Tepung Buah Lindur (Bruguiera gymnorhizza) terhadap Karakteristik Mutu Kue Kolombengi - Husain, Febriyanto; Naiu, Asri Silvana; Dali, Faiza A (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2023)
This research aims to determine the best substitution for lindur fruit flour (Bruguiera gymnorhizza) on the quality characteristics of Kolombengi cake. This research consisted of 3 stages, namely making lindur fruit flour (Bruguiera gymnorhizza), formulation of Kolombengi cake and characterization of the organoleptic and chemical quality of Kolombengi cake. The treatment in this research was a concentration of lindur fruit flour (Bruguiera gymnorhizza) of 30%, 40% and 50%, which is a substitute for wheat flour in making kolombengi cakes. Analysis of the data used for chemical testing uses analysis of variance (ANOVA), then the determination of the selected product is carried out using the Bayes test. The research results showed that the kolobengi cake which was substituted with lindur fruit flour with a concentration of 40% was the selected product which contained 12.52% water, 1.12% ash, 5.28% protein, 2.35% fat and 78.74% carbohydrates.